2011
DOI: 10.3382/japr.2009-00140
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of egg yolk color by paprika combined with a probiotic

Abstract: Enhancing egg yolk color by feeding laying hens paprika extract (Color-Up, Kohkin Chemical Co. Ltd., Higashiosaka, Japan; 5 g of xanthophylls/kg) and potentially accelerating the process by concurrent feeding of a probiotic (Balantol powder, Kohkin Chemical Co. Ltd.; 10 7 of lactic acid bacterium Enterococcus faecium BIO-4R/g) was examined. A total of 144 twentyfive-week-old laying hens were randomly assigned to 3 groups: a basal diet group (17.5% CP, 2,750 kcal of ME/kg; control), the basal diet plus 0.1% die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
3
12
1
Order By: Relevance
“…Paprika extract was more efficient in yolk pigmentation than marigold extract. Lokaewmanee et al (2011) noted that there was no associative effect of paprika and marigold on the egg yolk; however, different results were found by Moura et al (2011), who reported an associative effect of both extracts. Different results were reported by Englmaierová & Skrivan (2013) and Skrivan et al (2015), who obtained more colored yolk with the inclusion of marigold extract in laying hen diets when compared with the values obtained with corn-based diets.…”
Section: Resultsmentioning
confidence: 49%
“…Paprika extract was more efficient in yolk pigmentation than marigold extract. Lokaewmanee et al (2011) noted that there was no associative effect of paprika and marigold on the egg yolk; however, different results were found by Moura et al (2011), who reported an associative effect of both extracts. Different results were reported by Englmaierová & Skrivan (2013) and Skrivan et al (2015), who obtained more colored yolk with the inclusion of marigold extract in laying hen diets when compared with the values obtained with corn-based diets.…”
Section: Resultsmentioning
confidence: 49%
“…However, by adding 8% a change in performance was observed which reduced egg production to 46.7%. This is inconsistent with previous studies (Rowghani et al, 2006;Esfahani-Mashhour et al, 2009;Kijparkorn et al, 2010;Lokaewmanee et al, 2011), who found no significant production performance due to additives. Our study indicates that green algae fed at lower levels (T-1 and T-2) improves feed conversion ratio (FCR), explaining the nutrient content of green algae particularly protein have contributed to the egg production.…”
Section: Production Performancecontrasting
confidence: 57%
“…However, xanthophylls for yolk color only relied on corn were not able to satisfy the consumer's preferences due to the fact that total carotenoid of corn was only 22 mg/kg (Kijparkorn et al, 2010), which was lower than forage materials (Hammershøj et al, 2010). Therefore the use of several natural materials to improve yolk color have been implemented in layers such as marigold and skin orange (Hasin et al, 2006), marigold flower (MF), safflower petals (SP), red pepper meal (RPM) (Rowghani et al, 2006), sano flower (Kijparkorn et al, 2010), paprika (Lokaewmanee et al, 2011), turmeric root (TR) and annatto seed (AS) (Laganá et al, 2011) and duckweed in laying ducks (Indarsih and Tamsil, 2012). Indonesian small farmer cannot afford it because of limited commercial and natural availability as well as relatively expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Also, because these dried pulps contain 15.5 to 35.4 mg/100g (DM) of total carotenoid [6], they are considerable pigment sources. These pulps may be better pigment sources than yellow and red corns which contain 8.86 and 9.81 mg/100g (DM), respectively [7]. Second, egg yolk industry is very diverse and its color remains one of the best egg quality parameters for consumers [8,9].…”
Section: Introductionmentioning
confidence: 99%